2020
DOI: 10.1038/s41419-020-2657-z
|View full text |Cite
|
Sign up to set email alerts
|

Which long noncoding RNAs and circular RNAs contribute to inflammatory bowel disease?

Abstract: Inflammatory bowel disease (IBD), a chronic relapsing gastrointestinal inflammatory disease, mainly comprises ulcerative colitis (UC) and Crohn's disease (CD). Although the mechanisms and pathways of IBD have been widely examined in recent decades, its exact pathogenesis remains unclear. Studies have focused on the discovery of new therapeutic targets and application of precision medicine. Recently, a strong connection between IBD and noncoding RNAs (ncRNAs) has been reported. ncRNAs include microRNAs (miRNAs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 145 publications
0
31
0
Order By: Relevance
“…GPR25 is a G protein-coupled receptor that is highly expressed in T cells and NK cells and has been shown to be involved in the risk of MS and IBD 60 . In contrast, little is known about the function of lncRNAs AL133458.1, or of antisense gene LL22NC03-86G7.1 or pseudogene AC100854.1, but pseudogenes and non-coding RNAs have previously been hypothesised to make crucial contributions to comorbid MS 61,62 and IBD 63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…GPR25 is a G protein-coupled receptor that is highly expressed in T cells and NK cells and has been shown to be involved in the risk of MS and IBD 60 . In contrast, little is known about the function of lncRNAs AL133458.1, or of antisense gene LL22NC03-86G7.1 or pseudogene AC100854.1, but pseudogenes and non-coding RNAs have previously been hypothesised to make crucial contributions to comorbid MS 61,62 and IBD 63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs are considered important regulatory molecules in large numbers of biological processes involved in various diseases (Lin et al, 2020). An increasing number of studies have reported that circRNAs play important roles in the pathogenesis of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, correlations between circRIMS1 and clinical or pathological stages and histological grades will also be investigated. circRNAs have been reported to participate in the initiation and progression of sepsis, 43 schizophrenia, depression, 44 inflammatory bowel disease, 45 autoimmune diseases, 46 and especially human cancers. 47 , 48 , 49 , 50 , 51 , 52 Therefore, it is reasonable to speculate that they are also potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%